Defects in Hybrid Perovskites: The Secret of Efficient Charge Transport - Musiienko, Artem; Ceratti, Davide Raffaele; Pipek, Jindřich; Brynza, Mykola; Elhadidy, Hassan; Belas, Eduard; Betušiak, Marián; Delport, Geraud; Praus, Petr (WILEY-VCH, 2021)
The interaction of free carriers with defects and some critical defect properties are still unclear in methylammonium lead halide perovskites (MHPs). Here, a multi-method approach is used to quantify and characterize defects in single crystal MAPbI(3), giving a cross-checked overview of their properties. Time of flight current waveform spectroscopy reveals the interaction of carriers with five shallow and deep defects. Photo-Hall and thermoelectric effect spectroscopy assess the defect density, cross-section, and relative (to the valence band) energy. The detailed reconstruction of free carrier relaxation through Monte Carlo simulation allows for quantifying the lifetime, mobility, and diffusion length of holes and electrons separately. Here, it is demonstrated that the dominant part of defects releases free carriers after trapping; this happens without non-radiative recombination with consequent positive effects on the photoconversion and charge transport properties. On the other hand, shallow traps decrease drift mobility sensibly. The results are the key for the optimization of the charge transport properties and defects in MHP and contribute to the research aiming to improve perovskite stability. This study paves the way for doping and defect control, enhancing the scalability of perovskite devices with large diffusion lengths and lifetimes.

The interaction of free carriers with defects and some critical defect properties are still unclear in methylammonium lead halide perovskites (MHPs). Here, a multi-method approach is used to quantify and characterize defects in single crystal MAPbI(3), giving a cross-checked overview of their properties. Time of flight current waveform spectroscopy reveals the interaction of carriers with five shallow and deep defects. Photo-Hall and thermoelectric effect spectroscopy assess the defect density, cross-section, and relative (to the valence band) energy. The detailed reconstruction of free carrier relaxation through Monte Carlo simulation allows for quantifying the lifetime, mobility, and diffusion length of holes and electrons separately. Here, it is demonstrated that the dominant part of defects releases free carriers after trapping; this happens without non-radiative recombination with consequent positive effects on the photoconversion and charge transport properties. On the other hand, shallow traps decrease drift mobility sensibly. The results are the key for the optimization of the charge transport properties and defects in MHP and contribute to the research aiming to improve perovskite stability. This study paves the way for doping and defect control, enhancing the scalability of perovskite devices with large diffusion lengths and lifetimes.
Defects in Hybrid Perovskites: The Secret of Efficient Charge Transport
Keywords: charge transport; defects; halide perovskites; nature of defects; perovskites; perovskites stability; solar cells; charge transport; defects; halide perovskites; nature of defects; perovskites; perovskites stability; solar cells